2012
DOI: 10.1038/onc.2012.78
|View full text |Cite
|
Sign up to set email alerts
|

Minor cell-death defects but reduced tumor latency in mice lacking the BH3-only proteins Bad and Bmf

Abstract: Pro-apoptotic Bcl-2 family members of the BH3-only subgroup are critical for the establishment and maintenance of tissue homeostasis and can mediate apoptotic cell death in response to developmental cues or exogenously induced forms of cell stress and damage. Based on biochemical experiments as well as genetic studies in mice, the BH3-only proteins Bad and Bmf have been implicated in different proapoptotic events such as those triggered by glucose- or trophic factor-deprivation, glucocorticoids, or histone dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…However, double deficiency failed to delay spontaneous cell death of pro-B cells in culture (data not shown), consistent with barely detectable protein expression in these cells. 19 In contrast, when pre-B cells that express significant amounts of both proteins 19 were placed in culture and apoptosis was followed over time, we noted a significant delay of death in the absence of Bim. Additional loss of Bmf further augmented this resistance to spontaneous cell death in culture, although this effect was not very pronounced ( Figure 3A).…”
Section: Bim and Bmf Coregulate B Lymphopoiesismentioning
confidence: 72%
See 1 more Smart Citation
“…However, double deficiency failed to delay spontaneous cell death of pro-B cells in culture (data not shown), consistent with barely detectable protein expression in these cells. 19 In contrast, when pre-B cells that express significant amounts of both proteins 19 were placed in culture and apoptosis was followed over time, we noted a significant delay of death in the absence of Bim. Additional loss of Bmf further augmented this resistance to spontaneous cell death in culture, although this effect was not very pronounced ( Figure 3A).…”
Section: Bim and Bmf Coregulate B Lymphopoiesismentioning
confidence: 72%
“…This finding fits the rather poor expression of Bmf in mature T cells. 19 Notably, lymphocytes lacking For personal use only. on May 10, 2018. by guest www.bloodjournal.org From Bim and Puma do show a much broader spectrum of resistance phenotypes and are refractory to cytokine withdrawal, DNA damage, ER stress, pan-kinase inhibition, or glucocorticoid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…). While pro‐B cells express little Mcl1, pre‐B, immature, follicular and marginal zone B cells express higher but similar levels . Similarly, most thymocyte and mature T cell subsets show comparable Mcl1 expression and the protein is also prominently expressed outside the hematopoietic compartment.…”
Section: Introductionmentioning
confidence: 99%
“…15, 24 Studies in different cell types from bmf -deficient mice suggested, however, redundancy with other BH3-only proteins during the processes of apoptosis. 25, 26 …”
mentioning
confidence: 99%